Kesetaraan Gender “Perjuangan Perempuan dalam Menghadapi Diskriminasi” - Rinaldi Rinaldi; Yulfa Lumbaa (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The oppression of women is a lingering reality in many societies. It is important to continue fighting gender inequality and promoting women's rights. Solidarity and education are key in changing the mindset and systems that support such oppression. The purpose of this study is to provide a snapshot for women out there who are still blind to the prevailing system of patriarchy, encouraging women's awareness and understanding of gender inequality. Through the results of this study, it is hoped to motivate women to be actively involved in social change towards a more just and equal society. This research method is a Qualitative method with a library study approach, researchers look for information from a variety of clear sources, so that researchers can guarantee that this research is accurate. The results of this study show that there are already many Feminism movements that play an important role in voicing and fighting gender inequality. These findings reflect the growing awareness and participation of women in efforts to tear down the structure of patriarchy. Nonetheless, challenges remain, and this study confirms the need to continue to drive social change in order to achieve broader gender equality in a sustainable way for generations to come.